1981
DOI: 10.17016/ifdp.1981.184
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Exchange Rate Models of the Seventies: Are Any Fit to Survive?

Abstract: This study compares structural and time series models of exchange rate determination on the basis of their out-of-sample forecasting and explanatory power. We find that a random walk model would have outperformed all the other models as a predictor of the logarihm of major-country exchange rates during the 1970's.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
936
3
19

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 693 publications
(999 citation statements)
references
References 0 publications
41
936
3
19
Order By: Relevance
“…Following conventions in the literature, three benchmark models, random walk (RW), ARMA, and SVR model, are used in the model evaluation process [63]. The lag order for benchmark ARMA(r,m) during the forecasting process is set to ARMA(1,1).…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Following conventions in the literature, three benchmark models, random walk (RW), ARMA, and SVR model, are used in the model evaluation process [63]. The lag order for benchmark ARMA(r,m) during the forecasting process is set to ARMA(1,1).…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Most studies find that exchange rates follow martingale processes, so that the best forecast for time t + 1 is the value at time t (e.g. Meese and Singleton 1982;Meese and Rogoff 1983). Specifically, if S t is the logarithm of the exchange rate level then E t−1 (S t ) = S t−1 , where E t−1 is the conditional expectations operator as of time t − 1.…”
Section: Econometric Modelmentioning
confidence: 99%
“…Meese and Rogoff (1983a) showed that a random walk model of the exchange rate performed better in forecasting than any structural model. To date, this result still holds true, and as noted in Devereux (1997, p. 774), "this result has not been substantially overturned''.…”
Section: Forecasting Performance Of Estimated Modelsmentioning
confidence: 99%